PATTERN PRACTICE REVISITED: FROM SYNTAX TO SENSE AND POSITIVE EMOTIONS - Scheffler, Paweł; Butzkamm, Wolfgang (Neofilolog, 2019)
For many second and foreign language learners, the goal of language instruction is fluent oral performance. Such performance can be achieved if the mechanisms underlying L2 performance have been automatized. It is generally recognized that promoting automaticity in the classroom requires massive repetition and consistent practice, which, however, need to correspond to conditions of use in order for transfer into real speech to take place. It is also often acknowledged that meeting these requirements in classroom instruction is very difficult as traditional repetitive practice activities often take time away from communicative language use and fail to induce positive emotions in learners. In this article, we take a fresh look at the theory behind, and the implementation of, pattern practice. We begin by arguing that it is construction grammar that provides a theoretical oundation for pattern practice. We also demonstrate that monolingual drills in the audiolingual method marginalized meaning and were often mechanical. We then present bilingual drills as an alternative exercise type which facilitates pattern recognition, oral repetition and focus on meaning. We show that referring to the native language makes it possible to localize and individualize the examples used and to induce positive emotions in the process. Finally, we discuss communicative drills and use transcripts of classroom interaction to demonstrate that repetitive practice, communication and positive emotions can all be combined.